Evaluation of Variation in the Course of the Facial Nerve, Nerve Adhesion to Tumors, and Postoperative Facial Palsy in Acoustic Neuroma - Sameshima, Tetsuro; Morita, Akio; Tanikawa, Rokuya; Fukushima, Takanori; Friedman, Allan H.; Zenga, Francesco; Ducati, Alessandro; Mastronardi, Luciano (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective To investigate the variation in the course of the facial nerve (FN) in patients undergoing acoustic neuroma (AN) surgery, its adhesion to tumors, and the relationship between such adhesions and postoperative facial palsy.Methods The subjects were 356 patients who underwent AN surgery in whom the course of the FN could be confirmed. Patients were classified into six groups: ventro-central surface of the tumor (VCe), ventro-rostral (VR), ventro-caudal (VCa), rostral (R), caudal (C), and dorsal (D).Results The FN course was VCe in 185 cases, VR in 137, VCa in 19, R in 10, C in 4, and D in one. For tumors < 1.5 cm, VCe was most common. For tumors ≥ 1.5 cm, the proportion of VR increased. No significant difference was observed between the course patterns of the FN in terms of postoperative FN function, but for tumors > 3.0 cm, there was an increasing tendency for the FN to adhere strongly to the tumor capsule, and postoperative facial palsy was more severe in patients with stronger adhesions.Conclusions The VCe pattern was most common for small tumors. Strong or less strong adhesion to the tumor capsule was most strongly associated with postoperative FN palsy.
Keywords: acoustic neuromas; facial nerve; retrosigmoid approach; adhesion